Review and Critique of the Translation of the Book The Relevance of Natural Science to Theology - Ali Reza Farsi Nezhad (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Numerous books have been written or translated on the “relationship between science and religion” or “the relationship between science and theology.” One of these books is “The Relevance of Natural Science to Theology” by William H. Austin. This book is one of the few books that deals with the relationship between natural science and theology in a specialized and detailed way. The book has been translated by Ali Haqqi as “Relation of Natural Science to Theology”. The author sought to translate the content of the book into Persian, but found the translation so vague, inaccurate, and erroneous that he preferred to criticize the book’s translation in a critical-analytical way instead of criticizing the book’s content. The translation of this book is not suitable for any textbook or even a research source. Providing such translations with this volume of errors, for publication by the esteemed translator, and for publication by the esteemed publisher without prior professional judgment or at least without eliminating the apparent flaws should be seriously taken into account.